Domino Oxidative Cyclization of 2‐Aminoacetophenones for the One‐Pot Synthesis of Tryptanthrin Derivatives. Issue 36 (16th November 2015) - Reddy, B. V. Subba; Reddy, D. Maheswara; Reddy, G. Niranjan; Reddy, M. Ramana; Reddy, V. Krishna
Abstract: A new CuI/DMSO‐mediated oxidative domino process has been developed for the synthesis of tryptanthrin derivatives. This is the first example of the synthesis of tryptanthrin derivatives directly from 2‐aminoaryl methyl ketones and isatoic anhydrides through copper‐promoted oxidative functionalization. Abstract : A new DMSO/CuI‐catalysed oxidative domino process has been developed for the one‐pot synthesis of tryptanthrin derivatives.